Judeophobia and the New Testament texts and contexts - Rollens, Sarah E. 1984-; Vanden Eykel, Eric M.; Warren, Meredith J. C. (Grand Rapids, Michigan William B. Eerdmans Publishing Company, 2025)
"The spirit and voice of ancient ethnic bigotry (esp. anti-Semitism) rears its head time and again in the New Testament; the editors and contributors seek to explain, contextualize, engage, problematize, and offer pedagogical strategies for dealing with these difficult texts"--
Judeophobia in the undergraduate classroom / Christy Cobb -- Judeophobia in the seminary / Tom de Bruin -- The Pharisees / Meredith J.C. Warren, Shayna Sheinfeld, and Sara Parks.
Includes bibliographical references and indexes
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, interpretation, etc; Jews in the New Testament; Christianity and antisemitism -- History; Judaism (Christian theology) -- History of doctrines -- Early church, ca. 30-600; Aufsatzsammlung